PERAN DARI KOMITMEN DI DALAM RELATIONSHIP MARKETING TERHADAP RESPONS PENGGUNA DI MASKAPAI PENERBANGAN GARUDA INDONESIA SEBAGAI REPRESENTASI PERUSAHAAN MILIK NEGARA - Suluh Perbowo Santosa (Riset Manajemen dan Akuntansi, 2015)
This study aims: 1) Examine empirically the effect of the communication made by the company and the user trust against the user commitment; 2) Examine empirically the role of the dimensions of user commitment against the user response to the company. The sample in this study consisted of 139 users, using convenience sampling method. Calculation of validity test using Bivariate Correlation and reliability test using Cronbach's Alpha. The method of data analysis in this study using the classical assumption test, regression analysis, t test statistic, F test statistic, and R2. Based on the data analysis obtained the following results: 1) proved that the communication has positive and significant to the commitment; 2) proved that the trust has positive and significant to the commitment; 3) proved that the communication has positive and significant to the trust; 4) proved that the affective commitment has positive and significant to the repurchase intentions; 5) proved that the affective commitment has positive and significant to the advocacy (WOM); 6) proved that the continuance commitment has negative and significant to the advocacy (WOM); 7) proved that the affective commitment has positive and significant to the continuance commitment; 8) proved that the normative commitment has positive and significant to the affective commitment. Keywords : communication, trust, commitment, relationship marketing, consumer response, Garuda Indonesia